Experiment on road divider application: a case study in Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Research was carried out to investigate the existence of road divider. An experiment was conducted on J1. Magelang Yogyakarta to observe different conditions